PENGARUH LATIHAN RELAKSASI NAPAS DALAM TERHADAP TINGKAT STRES DAN TEKANAN DARAH MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAKARTA 2022 - Angelina Devora (2023)
The high prevalence of college students with moderate to severe stress levels and hypertension in Indonesia if not controlled may become the main contributor to heart disease and stroke which are in the top five causes of death, so a non-pharmacology treatment alternative is needed to reduce stress level and blood pressure, for example by doing deep breathing relaxation exercise. This research aims to see the effect of slow deep breathing to stress level and blood pressure. This research was conducted using the Pre-Experimental method with the One Group Pretest-Posttest design to 30 Faculty of Medicine students at Universitas Pembangunan Nasional Veteran Jakarta for 2 weeks to see whether deep breathing relaxation exercises can significantly reduce stress levels which were measured using the Perceived Stress Scale (PSS-10) and blood pressure. which was measured using a digital sphygmomanometer. The results showed that the majority of students experienced severe stress with a total of 83.33% which decreased to 66.67% after doing deep breathing relaxation exercises for 2 weeks, also the number of university students who were measured above normal decreased from 15 to 5 students for systolic blood pressure above normal and 3 students for diastolic blood pressure above normal, the result of the Paired T-Test on systolic blood pressure with a p value of 0.000 or <0.05 and the result of the Wilcoxon Signed Rank Test with a p value of 0.000 or <0.05 on diastolic blood pressure. This research concluded that breathing relaxation exercises can significantly reduce stress levels and blood pressure.